Empyema necessitatis due to Citrobacter freundii: Case report - Diego Andrés Rodríguez-Lugo (Revista de la Facultad de Medicina, 2018)
Introduction: This paper presents the first case of empyema necessitatis secondary to infection with Citrobacter freundii (according to the databases consulted), and one of the few reports of this pathology in Colombia.